USP9X Is Required to Maintain Cell Survival in Response to High-LET Radiation - Nickson, Catherine M.; Fabbrizi, Maria Rita; Carter, Rachel J.; Hughes, Jonathan R.; Kacperek, Andrzej; Hill, Mark A.; Parsons, Jason L. (Frontiers in Oncology, 2021)
Ionizing radiation (IR) principally acts through induction of DNA damage that promotes cell death, although the biological effects of IR are more broad ranging. In fact, the impact of IR of higher linear energy transfer (LET) on cell biology is generally not well understood. Critically therefore, the cellular enzymes and mechanisms responsible for enhancing cell survival following high-LET IR are unclear. To this effect, we have recently performed siRNA screening to identify deubiquitylating enzymes that control cell survival specifically in response to high-LET α-particles and protons, in comparison to low-LET X-rays and protons. From this screening, we have now thoroughly validated that depletion of the ubiquitin-specific protease 9X (USP9X) in HeLa and oropharyngeal squamous cell carcinoma (UMSCC74A) cells using small interfering RNA (siRNA), leads to significantly decreased survival of cells after high-LET radiation. We consequently investigated the mechanism through which this occurs, and demonstrate that an absence of USP9X has no impact on DNA damage repair post-irradiation, nor on apoptosis, autophagy or senescence. We discovered that USP9X is required to stabilize key proteins (CEP55 and CEP131) involved in centrosome and cilia formation, and plays an important role in controlling pericentrin-rich foci, particularly in response to high-LET protons. This was also confirmed directly by demonstrating that depletion of CEP55/CEP131 led to both enhanced radiosensitivity of cells to high-LET protons, and amplification of pericentrin-rich foci. Our evidence support the importance of USP9X in maintaining centrosome function and biogenesis, and which is crucial particularly in the cellular response to high-LET radiation.